COMPREHENSION PROCESSES AND CRITICAL THINKING SKILLS IN TWO UNIVERSITY ENTRANCE EXAMS IN INDONESIA: A CONTENT ANALYSIS OF THE SBMPTN AND THE SIMAK UI 2008-2019 - Bernard Richard Nainggolan; Pupung Purnawarman; Didi Sukyadi (Universitas Pelita Harapan, 2022)
Language testing development intervened with cognitive processes and higher-order thinking skills (HOTS) has impacted the English tests, included Indonesian university entrance exams within a decade. State universities in Indonesia which are in demand to the high quality of their candidates have conducted a highly reputable entrance exams to select their best candidates. However, less research was conducted to investigate the trend of English questions in the scope of university entrance tests. This study aimed to investigate trends of English questions tested in both the SBMPTN (national university entrance exams) and the SIMAK UI (Universitas Indonesia’s entrance exams) in a decade (from 2009 to 2018). The study design was a mixed-method employing content analysis to English questions (quantitatively and qualitatively). The findings revealed; 1) types of questions tested, 2) comprehension processes, 3) and higher-order thinking questions, and 4) construction MCQs to promote critical thinking skills in both entrance exams. Finally, implications of the findings were elaborated.Bahasa Indonesia Abstrak: Ujian Saringan Masuk (USM), khususnya soal bahasa Inggris, dipercaya dapat mengambarkan pemahamanan dan kemampuan berpikir kritis para kandidat. Oleh karena itu, penelitian terhadap USM menjadi sangat signifikan. Nyatanya, penelitian tentang USM sangat jarang dan tren terhadap soal-soal bahasa Inggris terbatas. Penelitian ini bertujuan untuk menyelidiki tren dalam proses pemahaman dan kemampuan berpikir tingkat tinggi yang termanifestasi dalam Ujian Seleksi Masuk UI (SIMAK UI) dalam satu dekade belakangan (2009-2018). Dengan menggunakan metode campuran content analysis, pertanyaan-pertanyaan dianalisa secara kualitatif dan kuantitatif dan menghasil beberapa temuan seperti 1) jenis pertanyaan yang diuji, 2) proses pemahaman, 3) pertanyaan untuk kemampuan berpikir tingkat tinggi, dan 4)konstruksi pembuatan pertanyaan pilihan ganda yang bertujuan meningkatkan kemampuan berpikir kritis. Implikasi dari temuan ini juga dijelaskan.